Ascorbic acid as an effective alternative for treatment of dapsone poisoning in a child: A case report (Indian Journal of Case Reports, 2017)
Dapsone (DDS – Diamino diphenyl sulfone), a sulfonamide derivative acts by inhibiting PABA incorporation into folic acid. It is commonly used in treating skin diseases. Accidental poisoning in children is uncommon. It results in methaemoglobinemia by causing oxidative stress. Principle of treatment relies on treating methemoglobinemia by using reducing agents like methylene blue or ascorbic acid. Due to the long half-life, dapsone provides a continuing oxidative stress that can cause a recurrence of clinically significant methaemoglobinaemia and hence takes long to treat. Ascorbic acid is effective in treating methemoglobinemia associated with dapsone poisoning as demonstrated in this case report of a four and half year old child’s accidental ingestion of dapsone tablets and presenting with cyanosis. The child was managed successfully with ascorbic acid and supportive treatment.